Lithium-rich manganese-based positive electrode material and preparation method thereof

Mg doped precursor is prepared by co-precipitation method, and Na and Se are added during the sintering process to form a lithium-rich manganese-based positive electrode material doped with Na, Mg, and Se, which solves the problem of reducing discharge specific capacity caused by structural changes in the material during charging and discharging, and achieves the improvement of the structural stability and electrochemical performance of the material.

CN119503909AActive Publication Date: 2025-02-25GUANGXI YINYI HIGH TECH R & D CO LTD +1

Patent Information

Application Number
CN202411626184.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The structure of the lithium-rich manganese-based positive electrode material changes during the charging and discharging process, resulting in a decrease in the discharge specific capacity, affecting its rate performance and cycling performance.

Method used

The Mg-doped precursor is prepared by co-precipitation method, and Na and Se are added during the sintering process to form a lithium-rich manganese-based positive electrode material doped with Na, Mg, and Se. The structure of the material is stabilized and its electrochemical properties are improved.

Benefits of technology

Through this method, the discharge specific capacity of the first circle of the material and the capacity retention rate of 100 circles are improved, the structure of the material is stabilized, and its rate performance and cycle performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503909A_ABST
    Figure CN119503909A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a lithium-rich manganese-based positive electrode material and a preparation method thereof, and the preparation method comprises the following steps: (1) preparing an Mg-doped precursor; (2) synthesizing an Mg-doped positive electrode material; (3) synthesizing a positive electrode material doped with Mg and Na; and (4) synthesizing the anode material doped with Mg, Na and Se. Non-electrochemical active elements Mg, Na and Se are used for replacing part of elements of the positive electrode material, and the sintered positive electrode material is not prone to structural transformation in the charging and discharging process, so that the performance is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] At present, the positive electrode materials of mainstream power batteries, such as lithium iron phosphate batteries, nickel-cobalt-manganese ternary lithium batteries, and lithium cobalt oxide batteries, have relatively low specific capacity and their performance is close to a bottleneck. It is urgent to develop new power battery positive electrode materials to meet the requirements. In recent years, the emergence of lithium-rich manganese-based positive electrode materials is expected to solve the pain point of low capacity of current positive electrode materials. The lithium-rich manganese-based positive electrode material xLi2MnO3·(1-x)LiMO2 (M=Mn, Co, Ni, etc.)) has become the focus of scientific researchers due to its high specific capacity, low price, and environmental friendliness.

[0003] Lithium-rich manganese-based cathode materials contain more manganese elements, are relatively cheap to produce, have good safety, and are environmentally friendly. The monoclinic phase of Li2MnO3 in the material not only stabilizes the structure, but also provides additional capacity, so that the overall discharge capacity of the material is further improved. Although the performance of lithium-rich manganese-based cathode materials is relatively superior, their first coulombic efficiency is low. During the charge and discharge cycle, the material gradually changes from a layered structure to a spinel-like structure, resulting in an unstable overall structure of the material, as well as capacity attenuation, voltage attenuation, and poor rate capability, which to a certain extent affect its practicality. Therefore, in recent years, many researchers have conducted a large number of modification studies on lithium-rich manganese-based materials, such as bulk doping, surface coating, and new structure design and construction. Traditional element doping and surface coating have a certain effect on improving the electrochemical performance of the material, but different modification methods have different improvement effects. At present, a single modification method cannot fundamentally solve the problems faced by the material. Therefore, it is necessary to adopt a combination of multiple modification methods and develop new structures (such as single crystal structure, composite structure, composition regulation and gradient structure, etc.) to solve the problems faced by the material. In addition, the structure and composition design of the lithium-rich manganese-based positive electrode material precursor is also very important. It is necessary to consider both the high capacity of the material and the density improvement to achieve a relative balance between capacity and density.

[0004] Patent No. CN202011100886.9 proposes a dual-system co-precipitation method to prepare a lithium-rich manganese-based precursor co-doped with fluorine and magnesium. The cathode material prepared from this precursor effectively improves the material's crystal stability and inhibits voltage decay, and has excellent electrochemical performance. However, when fluorine and magnesium are doped into the precursor material at the same time, the uncontrollable factors in the preparation process increase, and the control of the precursor morphology and precipitation components becomes more difficult.

[0005] The doctoral dissertation of Central South University studied the effect of Se dopants on the electrochemical properties, morphology and structural characteristics of ternary cathode materials. After research, Se was doped into the ternary cathode material, with a first-cycle discharge capacity of 293.5 mAh / g and a coulombic efficiency of 94.3%. At a current density of 1C, after 400 cycles, there was still an 88.4% capacity retention rate, which was better than the undoped cathode material.

[0006] Starting from the structure of lithium-rich manganese-based materials, the present invention explores a preparation method that can stabilize its structure, thereby improving its charge and discharge cycle performance and rate capability, and providing ideas for industrialization. Summary of the invention

[0007] In order to solve the problem in the prior art that the structure of lithium-rich manganese-based positive electrode materials changes during the charge and discharge process, resulting in a decrease in discharge specific capacity, and to further improve the rate performance and cycle performance of the material, the present invention provides a lithium-rich manganese-based positive electrode material and a preparation method thereof.

[0008] The technical solution of the present invention is as follows:

[0009] A method for preparing a lithium-rich manganese-based positive electrode material comprises the following steps:

[0010] (1) taking nickel salt, cobalt salt, manganese salt and magnesium salt to prepare a mixed salt solution; using NH3HCO3 as a buffer base solution, adding a precipitant, a complexing agent and the mixed salt solution to react, and performing an aging treatment after the reaction is completed to obtain a Mg-doped precursor;

[0011] (2) taking the Mg-doped precursor of step (1), adding lithium salt and sodium salt, mixing thoroughly and sintering, the sintering atmosphere is air, and obtaining a Mg-doped and Na-doped positive electrode material;

[0012] (3) Take the Mg and Na doped positive electrode material of step (2), crush it, add Se powder, mix it evenly, and sinter it in an inert atmosphere to obtain a Na, Mg, Se doped lithium manganese-based positive electrode material.

[0013] Furthermore, in step (1), in the mixed salt solution, the molar ratio of nickel, cobalt, manganese and magnesium is 0.13:0.13:0.52:0.02.

[0014] Furthermore, in step (1), the nickel salt is selected from one or more of water-soluble NiSO4, Ni(NO3)2, and Ni(CH3COO)2; the cobalt salt is selected from one or more of water-soluble CoSO4, Co(NO3)2, and Co(CH3COO)2; the manganese salt is selected from one or more of MnSO4, Mn(NO3)2, and Mn(CH3COO)2; and the magnesium salt is selected from one or more of MgSO4, Mg(NO3)2, and Mg(CH3COO)2.

[0015] Furthermore, in step (1), the complexing agent is aqueous ammonia; and the precipitating agent is selected from one or more of Na2CO3, NaHCO3, NH4HCO3, (NH4)2CO3, and K2CO3.

[0016] Furthermore, in step (1), during the reaction, the pH is controlled between 8.5-9.5 and the temperature is controlled between 55°C and 65°C.

[0017] Preferably, in step (2), the lithium salt is selected from one or more of lithium hydroxide, lithium carbonate, lithium nitrate, and lithium acetate; the sodium salt is selected from one or more of sodium carbonate, sodium nitrate, and sodium bicarbonate; and the sintering is carried out in an air atmosphere, with a first stage at 400-600° C. for 4-6 hours, a second stage at 900-980° C. for 10-15 hours, and a heating rate of 3° C. / min.

[0018] Preferably, in step (3), the sintering is carried out in an inert atmosphere at a sintering temperature of 550-650° C. for 4-7 hours.

[0019] A lithium-rich manganese-based positive electrode material is prepared by the above-mentioned method for preparing the lithium-rich manganese-based positive electrode material.

[0020] The process of the present invention is as follows Figure 1 shown.

[0021] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0022] (1) The production of precursors in a small reactor using the more traditional co-precipitation method can be scaled up and applied to actual production to achieve industrialization;

[0023] (2) Weakly alkaline carbonates are used as precipitants, which are safer than other hydroxide precipitants, and the low pH solution is easy to neutralize and is environmentally friendly;

[0024] (3) Using non-electrochemically active elements Mg, Na, and Se to replace some elements of the positive electrode material, the positive electrode material after sintering is not prone to structural transformation during the charge and discharge process, thus stabilizing the performance;

[0025] (4) The high-temperature solid phase method is used for sintering, and the sintering operation can be completed without adding special equipment or devices, thus reducing investment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a process flow chart of the present invention;

[0027] Figure 2 Figure 1 is a scanning electron microscope image of the precursor; Figure a is the undoped precursor of Comparative Example 1, and Figure b is the Mg-doped precursor of Example 1;

[0028] Figure 3 This is the XRD diagram of Example 1. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] (1) nickel salt, cobalt salt, manganese salt and magnesium salt are prepared into a 2 mol / L mixed salt solution, wherein the molar ratio of nickel, cobalt, manganese and magnesium is 0.13:0.13:0.52:0.02; 0.2 mol / L NH3HCO3 is used as a buffer base liquid, and a precipitant, a complexing agent and the mixed salt solution are pumped in for reaction, wherein the pumping flow rates are: mixed salt solution 1 ml / min, complexing agent 0.75 ml / min, and the precipitant flow rate is automatically adjusted according to the pH change of the equipment, and nitrogen is introduced for protection to prevent oxidation, and the pH is controlled to be 9.0, the temperature is 60°C, the stirring speed is 50 rpm / min, the reaction time is 15 h, and the aging is performed for 20 h, and then filtered, washed with deionized water for many times, and dried at 110°C for 15 h to obtain a Mg-doped precursor; wherein the precipitant is sodium carbonate, the solution concentration is 2 mol / L, and ammonia water is used as the complexing agent, and the solution concentration is 0.5 mol / L;

[0032] (2) Take the Mg-doped precursor of step (1), add lithium carbonate and sodium carbonate, mix well and then sinter. The sintering atmosphere is air. The first stage is kept at 500°C for 4 hours, and the second stage is kept at 950°C for 12 hours. The heating rate is 3°C / min. The sintered product is ground and sieved to obtain Mg-doped and Na-doped positive electrode materials. The amount of lithium carbonate and sodium carbonate is based on the Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.52 Mg 0.02 O2 chemical formula calculation, wherein lithium carbonate is added at 105% of the theoretical amount;

[0033] (3) Take the Mg and Na-doped positive electrode material of step (2), crush it, and add Se powder (the amount of Se powder added is based on Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.52 Mg 0.02 O1.975 Se 0.025 Chemical formula calculation), mixed evenly, sintered in argon atmosphere at a temperature of 600°C for 5 hours; the sintered selenized lithium-rich manganese-based positive electrode material was washed several times with CS2 and anhydrous ethanol solution, vacuum dried at 120°C for 10 hours, ground into powder, sieved, and obtained Na, Mg, Se-doped lithium-rich manganese-based positive electrode material Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.5 2Mg 0.02 O 1.975 Se 0.025 .

[0034] Example 2

[0035] The steps of Example 2 are basically the same as those of Example 1, except that: in step (1), during the reaction, the pH is controlled between 8.5 and the temperature is 55°C; in step (2), the sintering is carried out in an air atmosphere, with the first stage being kept at 400°C for 5 hours and the second stage being kept at 900°C for 10 hours, with a heating rate of 3°C / min; in step (3), the sintering is carried out in an argon atmosphere, with a sintering temperature of 550°C, and selenization sintering is carried out for 4 hours.

[0036] Example 3

[0037] The steps of Example 2 are basically the same as those of Example 1, except that: in step (1), during the reaction, the pH is controlled between 9.5 and the temperature is 65°C; in step (2), the sintering is carried out in an air atmosphere, with the first stage being kept at 600°C for 6 hours and the second stage being kept at 980°C for 15 hours, and the heating rate is 3°C / min; in step (3), the sintering is carried out in an argon atmosphere, with a sintering temperature of 650°C, and selenization sintering is carried out for 7 hours.

[0038] Comparative Example 1

[0039] The difference from Example 1 is that the Li prepared in Comparative Example 1 is undoped 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 lithium-rich manganese-based positive electrode material.

[0040] The preparation steps are as follows:

[0041] (1) nickel salt, cobalt salt and manganese salt are prepared into a 2 mol / L mixed salt solution, wherein the molar ratio of nickel, cobalt and manganese is 0.13:0.13:0.54; 0.2 mol / L NH3HCO3 is used as a buffer base liquid, and a precipitant, a complexing agent and the mixed salt solution are pumped in for reaction, wherein the pumping flow rates are: mixed salt solution 1 ml / min, complexing agent 0.75 ml / min, and the precipitant flow rate is automatically adjusted according to the pH change of the equipment, and nitrogen is introduced for protection to prevent oxidation, and the pH is controlled to be 9.0, the temperature is 60°C, the stirring speed is 50 rpm / min, the reaction time is 15 h, and the aging is performed for 20 h, and then filtered, washed with deionized water for many times, and dried at 110°C for 15 h to obtain a precursor; wherein the precipitant is sodium carbonate, the solution concentration is 2 mol / L, and ammonia water is used as the complexing agent, and the solution concentration is 0.5 mol / L;

[0042] (2) Take the precursor of step (1), add lithium carbonate, mix thoroughly and then sinter. The sintering atmosphere is air. The first stage is kept at 500°C for 4 hours, and the second stage is kept at 950°C for 12 hours. The heating rate is 3°C / min. The sintered product is ground and sieved to obtain undoped Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 lithium-rich manganese-based positive electrode material; the amount of lithium carbonate used is based on Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.54 O2 chemical formula calculation, wherein lithium carbonate is added according to 105% of the theoretical amount.

[0043] Comparative Example 2

[0044] The difference from Example 1 is that the Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.54 O2 lithium-rich manganese-based positive electrode material.

[0045] The specific steps are as follows:

[0046] (1) nickel salt, cobalt salt and manganese salt are prepared into a 2 mol / L mixed salt solution, wherein the molar ratio of nickel, cobalt and manganese is 0.13:0.13:0.54; 0.2 mol / L NH3HCO3 is used as a buffer base liquid, and a precipitant, a complexing agent and the mixed salt solution are pumped in for reaction, wherein the pumping flow rates are: mixed salt solution 1 ml / min, complexing agent 0.75 ml / min, and the precipitant flow rate is automatically adjusted according to the pH change of the equipment, and nitrogen is introduced for protection to prevent oxidation, and the pH is controlled to be 9.0, the temperature is 60°C, the stirring speed is 50 rpm / min, the reaction time is 15 h, and the aging is performed for 20 h, and then filtered, washed with deionized water for many times, and dried at 110°C for 15 h to obtain a precursor; wherein the precipitant is sodium carbonate, the solution concentration is 2 mol / L, and ammonia water is used as the complexing agent, and the solution concentration is 0.5 mol / L;

[0047] (2) Take the precursor of step (1), add lithium carbonate and sodium carbonate, mix well and then sinter. The sintering atmosphere is air. The first stage is kept at 500°C for 4 hours, and the second stage is kept at 950°C for 12 hours. The heating rate is 3°C / min. The sintered product is ground and sieved to obtain Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.54 O2 lithium-rich manganese-based positive electrode material; the amount of lithium carbonate and sodium carbonate is based on Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.54 O2 chemical formula calculation, wherein lithium carbonate is added according to 105% of the theoretical amount.

[0048] Comparative Example 3

[0049] The difference from Example 1 is that the Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.54 O 1.975 Se 0.025 Lithium-rich manganese-based positive electrode material.

[0050] The specific steps are as follows:

[0051] (1) nickel salt, cobalt salt and manganese salt are prepared into a 2 mol / L mixed salt solution, wherein the molar ratio of nickel, cobalt and manganese is 0.13:0.13:0.54; 0.2 mol / L NH3HCO3 is used as a buffer base liquid, and a precipitant, a complexing agent and the mixed salt solution are pumped in for reaction, wherein the pumping flow rates are: mixed salt solution 1 ml / min, complexing agent 0.75 ml / min, and the precipitant flow rate is automatically adjusted according to the pH change of the equipment, and nitrogen is introduced for protection to prevent oxidation, and the pH is controlled to be 9.0, the temperature is 60°C, the stirring speed is 50 rpm / min, the reaction time is 15 h, and the aging is performed for 20 h, and then filtered, washed with deionized water for many times, and dried at 110°C for 15 h to obtain a precursor; wherein the precipitant is sodium carbonate, the solution concentration is 2 mol / L, and ammonia water is used as the complexing agent, and the solution concentration is 0.5 mol / L;

[0052] (2) Take the precursor of step (1), add lithium carbonate and sodium carbonate, mix well and then sinter. The sintering atmosphere is air. The first stage is kept at 500°C for 4 hours. The second stage is kept at 950°C for 12 hours. The heating rate is 3°C / min. The sintered product is ground and sieved to obtain Mg-doped and Na-doped positive electrode materials. The amount of lithium carbonate and sodium carbonate is based on the Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.54 O2 chemical formula calculation, wherein lithium carbonate is added at 105% of the theoretical amount;

[0053] (3) Take the Mg and Na-doped positive electrode material of step (2), crush it, and add Se powder (the amount of Se powder added is based on Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.54 O 1.975 Se 0.025 Chemical formula calculation), mixed evenly, sintered in argon atmosphere at a temperature of 600°C for 5 hours; the sintered selenized lithium-rich manganese-based positive electrode material was washed several times with CS2 and anhydrous ethanol solution, vacuum dried at 120°C for 10 hours, ground into powder, sieved, and obtained Na, Mg, Se-doped lithium-rich manganese-based positive electrode material Li 1.18 Na 0.02 Ni 0.13 Co 0.13 Mn 0.5 4O 1.975 Se 0.025 .

[0054] Electrochemical performance test:

[0055] The lithium-rich manganese-based positive electrode materials of Examples 1-3 and Comparative Examples 1-3 were prepared into button batteries to test the electrochemical performance. The battery preparation and testing methods are as follows: accurately weigh the lithium-rich manganese-based positive electrode material, acetylene black and PVDF dissolved in NMP in a mass ratio of 8:1:1, mix them into a slurry, and apply the slurry on the aluminum collector foil. Subsequently, the aluminum foil is placed in a vacuum oven at 110°C and dried for 30 minutes to vaporize the NMP. The dried aluminum foil is rolled, and the aluminum foil punch is placed in a vacuum oven and dried at 110°C for 12 hours to obtain a positive electrode sheet. A lithium metal sheet is used as the negative electrode. PP / PE polymer is used as a diaphragm to separate the positive and negative electrodes, and a solution of 1 mol / LLiPF6 in EC / EMC / DMC is used as the electrolyte to assemble the CR2032 button half-cell in an argon-filled glove box. The battery test system was used to test and analyze the battery charge and discharge cycle. The cycle test was carried out in a temperature-controlled experimental chamber at 25°C. All batteries were left to rest for 2 hours before testing, and then activated at a rate of 0.1C (1C = 220mA / g) in the voltage range of 2.0-4.7V. The later cycle charge and discharge rate was 0.1C, and the cycle was 100 times.

[0056] Table 1 shows the electrochemical performance of various embodiments and comparative examples:

[0057] Table 1

[0058]

[0059] From Table 1, we can see that:

[0060] (1) It can be seen from Examples 1-3 that the 0.1C first cycle discharge specific capacity is relatively high, indicating that Mg has been doped into the transition metal layer of the material, which plays a role in stabilizing the structure of the material during the charge and discharge process. The capacity retention rate after 100 cycles is also maintained at a high level.

[0061] (2) Compared with Example 1, Comparative Examples 1 and 2, the first cycle discharge specific capacity is reduced because Na is electrochemically inactive, and doping replaces part of the Li position to reduce the capacity. However, it plays a supporting role in the Li layer during the charge and discharge process, allowing Li to be smoothly removed and embedded. The capacity retention rate of 100 cycles increases with the incorporation of Na.

[0062] (3) Comparative Example 1 and Comparative Examples 2-3, as Se is doped into the oxygen position, the capacity retention rate of 100 cycles is further improved. This is because during the charge and discharge process, lattice oxygen in the Li2MnO3 phase will escape to form oxygen release. This process is irreversible. Se doping can effectively reduce this process, thereby improving the structural stability of the material and improving the capacity retention rate.

[0063] (4) Comparing Examples 1-3, the second-stage sintering temperature has an impact on the first-cycle discharge capacity and the 100-cycle capacity retention rate. When the sintering temperature is low, the structure of the positive electrode material is less stable, and the first-cycle discharge capacity and the 100-cycle capacity retention rate are relatively low; when the sintering temperature is higher, the structure is more stable, and the 100-cycle capacity retention rate is relatively high, but the electrochemical active substance is more difficult to be removed and embedded in the material, and the discharge capacity is relatively reduced.

[0064] Scanning Electron MicroscopeSEM

[0065] Figure 2 It is a scanning electron microscope image of the precursor; Figure a is the undoped precursor of comparative example 1, and Figure b is the Mg-doped precursor of embodiment 1. It can be seen from the figure that the surface of the Mg-doped sphere is loose, and during the sintering process, the Li element can diffuse more quickly inside the sphere and is evenly distributed inside the material, so that the material has good electrochemical properties.

[0066] Figure 3 The XRD diagram of Example 1 shows that the (006) / (012) peak and the (018) / (110) peak split significantly, indicating that the material has a good layered structure, which is beneficial to Li + Extraction and embedding. The typical Li2MnO3 diffraction peak is between 2θ=20°-25°, belonging to the C2 / m space group, which is the main feature of lithium-rich manganese-based materials.

[0067] In the above embodiments and comparative examples, the nickel salt is selected from NiSO4, and those skilled in the art may also choose one or more of water-soluble Ni(NO3)2 and Ni(CH3COO)2 according to common sense; the cobalt salt is selected from CoSO4, and those skilled in the art may also choose one or more of water-soluble Co(NO3)2 and Co(CH3COO)2 according to common sense; the manganese salt is selected from MnSO4, and those skilled in the art may also choose one or more of Mn(NO3)2 and Mn(CH3COO)2 according to common sense; the magnesium salt is selected from MgSO4, and those skilled in the art may also choose one or more of Mg(NO3)2 and Mg(CH3COO)2 according to common sense.

[0068] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A method for preparing a lithium-rich manganese-based positive electrode material, characterized in that The steps include: (1) taking nickel salt, cobalt salt, manganese salt and magnesium salt to prepare a mixed salt solution; using NH3HCO3 as a buffer base solution, adding a precipitant, a complexing agent and the mixed salt solution to react, and performing an aging treatment after the reaction is completed to obtain a Mg-doped precursor; (2) taking the Mg-doped precursor of step (1), adding lithium salt and sodium salt, mixing thoroughly and sintering, the sintering atmosphere is air, and obtaining a Mg-doped and Na-doped positive electrode material; (3) Take the Mg and Na doped positive electrode material of step (2), crush it, add Se powder, mix it evenly, and sinter it in an inert atmosphere to obtain a Na, Mg, Se doped lithium manganese-based positive electrode material.

2. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (1), in the mixed salt solution, the molar ratio of nickel, cobalt, manganese and magnesium is 0.13:0.13:0.52:0.

02.

3. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (1), the nickel salt is selected from one or more of water-soluble NiSO4, Ni(NO3)2, and Ni(CH3COO)2; the cobalt salt is selected from one or more of water-soluble CoSO4, Co(NO3)2, and Co(CH3COO)2; the manganese salt is selected from one or more of MnSO4, Mn(NO3)2, and Mn(CH3COO)2; the magnesium salt is selected from one or more of MgSO4, Mg(NO3)2, and Mg(CH3COO)2.

4. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (1), the complexing agent is ammonia water; the precipitating agent is selected from one or more of Na2CO3, NaHCO3, NH4HCO3, (NH4)2CO3, and K2CO3.

5. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (1), during the reaction, the pH is controlled between 8.5-9.5 and the temperature is controlled between 55°C and 65°C.

6. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (2), the lithium salt is selected from one or more of lithium hydroxide, lithium carbonate, lithium nitrate, and lithium acetate; the sodium salt is selected from one or more of sodium carbonate, sodium nitrate, and sodium bicarbonate; the sintering is carried out in an air atmosphere, with a first stage at 400-600° C. for 4-6 hours, a second stage at 900-980° C. for 10-15 hours, and a heating rate of 3° C. / min.

7. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: In step (3), the sintering is carried out in an inert atmosphere at a sintering temperature of 550-650° C. for 4-7 hours of selenization sintering.

8. A lithium-rich manganese-based positive electrode material, characterized in that: The lithium-rich manganese-based positive electrode material is prepared by the preparation method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Lithium-rich manganese-based precursors and their preparation methods, lithium-rich manganese-based cathode materials and their preparation methods, lithium-ion batteries

    CN112234176B

  • Doped and coated nickel-cobalt-aluminum-manganese quaternary lithium-ion battery positive electrode material, preparation method and application

    CN109473657A

  • Anion-cation co-doped high-nickel single-crystal ternary positive electrode material as well as preparation method and application thereof

    CN113764658A

  • High-rate single-crystal high-nickel positive electrode material as well as preparation method and application thereof

    CN114843502A

  • Composite positive active material, positive electrode and lithium battery containing the composite positive active material

    US20170062813A1

Cited By

  • Doped and coated lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN120376619A

  • Tellurium element modified cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

    CN121149231A